Optical band gap and ir spectra of glasses in the system [Nd2O3](r)-[CuO](35-x)-[P2O5](65) - Sahar, Md. Rahim; Budi, Agus Setyo (Malaysian Solid State Science and Technology Society, 2006)
The infra red and ultraviolet-visible spectroscopiy of neodymium copper phosphate glasses on the [Nd2O3](x)-[CuO](35-x)-[P2O5](65) system with 0<x<10 mol % has been studied. The study shows existence of phosphate tetrahedral dominates in lattice vibrations. It is also found out that The Urbach energy lie between 0.451 and 0.634 eV, and the optical energy gaps between 0.79 eV to 2.34 Â± 0.01eV.